COVID-19 - reflections on the surprise of both an expected and unexpected event - Johannes Platje; Jeffrey Harvey; Lez Rayman-Bacchus (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This paper reflects on the COVID-19 epidemic from the perspective of small probabilities and the difficulty of predicting similar events. Against the background of basic economic principles, the importance of the precautionary principle for crisis management is discussed, as well as potential consequences of this epidemic. ~ Findings: The authors argue that whilst the epidemic as such was unexpected, in future countries should be prepared for such stochastic events to happen. This requires a precautionary approach. When society is not prepared for such a calamity, or waits too long to implement measures to deal with it, the social and economic costs may be very high - much higher than 'hedging bets' and losing. The article reflects on different issues which are meant for further discussion on unpredictable future threats. One important issue is the uncertainty created by this event. This increases the likeliness that something unexpected can appear in the near future, creating the need for research and discussion on public and government responses to these events. Being aware of such challenges increases the likeliness of society and people to be prepared for such developments. It is concluded that the current crisis brings forward the question whether the current political-economic system and globalization makes future pandemics more likely, and whether a radical change towards a more locally oriented economy provides solutions that minimize the likelihood or frequency of future pandemics.
Keywords: 330